IMPLEMENTASI PERMAINAN TEBAK KATA DALAM PEMBELAJARAN ANAK USIA DINI DI RA TUNAS MULIA DUA - Nitsailla Haditsti; Ika Ratih Sulistiani; Eko Setiawan (UNISMA, 2022)
Early childhood has a special role so that education for early childhood becomes an important need for all parties. Basically every educational institution has its own advantages. The public's view of graduation achievement with the predicate of fluent reading ability causes educational institutions to make reading activities with the target of graduating from school can read fluently. Through playing learning activities are more meaningful, fun, and children can easily accept the activity material. Likewise with reading activities that can be done by playing.the source of this research data is group B in RA Tunas Mulia Dua. The results showed that word guessing games were carried out in two ways, first using educational game tools and second without using educational game tools that could improve children's vocabulary and the quality of children's learning. The word guessing game is adapted to the theme and lesson plan designed by the class teacher.